Cash Holdings, Dividend Payout, and Corporate Value: The Role of Institutional Investors - Hendra Wijaya (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
This study examines the relationship between cash holdings and dividend payout on corporate value. The moderating effect of institutional investors on the effect of cash holdings and dividend distribution on corporate value is also investigated in this study. This study applied nonfinancial companies listed on the Indonesia Stock Exchange between 2015 and 2019 and a total of 1269 observations. The data in this study were analyzed using the ordinary least squares method. According to the findings of the study, cash holdings have a positive influence on the value of the company. However, corporate value is unaffected by dividend payout. The findings of this investigation suggest that institutional investors do not moderate the impact of cash holdings on corporate value. However, institutional investors moderate the impact of dividend payout positively. This paper elaborates on institutional investors, a mechanism for agency conflict in relation to cash holdings, dividend payout, and corporate value.